Electrocatalytic Oxidation of Methanol by a Polymeric Ni Complex-Modified Electrode Prepared by a One-Step Cold-Plasma Process - Jeon, Ji-Soo; Yu, In-Keun; Kim, Woonjung; Choi, Seong-Ho (Frontiers in Chemistry, 2020)
In this work, a polymeric nickel complex-modified ITO electrode was prepared by a one-step cold-plasma process of acrylic-Ni complex precursors. The acrylic-Ni complex precursors were synthesized by complexation of nickel (II) chloride, and acrylic acid in a small amount of water; subsequently we added N,N’-methylene-bis-acrylamide as a crosslinking agent to the complex solution. We characterized the prepared polymeric Ni complex-modified (Ni-modified) catalytic electrode by X-ray photoelectron spectroscopy, field emission scanning electron microscopy, and electrochemical methods. Electrochemical characterization showed stable redox behavior of Ni(III)/Ni(II) couples. Cyclic voltammetric experiments have shown that electrocatalytic oxidation of methanol can occur on Ni-modified catalytic electrodes, while not observed on bare ITO.